Role of cognitive prompts in video caregiving training for older adults: optimizing deep and surface learning. Issue 1 (2nd January 2019) - Smith, Derek; Zheng, Robert; Metz, Aj; Morrow, Sue; Pompa, Janience; Hill, Justin; Rupper, Rand
ABSTRACT: Enhancing the cognitive functionality of digital technology can be critical in learning complex topics like caregiving for older adults. This study examines the deployment of cognitive prompts in video-based training to optimize older adults' cognitive information process in both deep and surface learning. The path analysis revealed the relationship among cognitive prompts, crystallized knowledge and learning outcomes showing crystallized knowledge as a significant mediator between cognitive prompts and learning outcomes. Additionally, cognitive prompts were shown to be significant in activating older learners' prior knowledge, rendering the learning process more meaningful and purposeful for older adults.